Basic aspects of radio electronic defence for system of radio contact of tactical link of management of Interior Troops, MIA, Ukraine during implementation of tasks software setting in the conditions of city - Iohov О. Yu.; Antonets, V. V.; Horbov, O. M.; Kuzminich, I. V.; Ovcharenko, V. V. (Honor and Law, 2019)
The basic problem questions of providing of radio electronic defence of the system of radio contact of IT, MIA, Ukraine. Аre considered, a structure and basic concepts of radio electronic defence is certain. Directions of subsequent scientific researches are grounded..